Enhancing Critical Thinking and Scientific Literacy through Scratch 3D–Supported Problem-Based Learning in Kinematics - Perdana, Riki; Arga Cetta, Atthaya Rafi; Sukardiyono, Sukardiyono; Pradana, Pramudya Wahyu (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2026)
Developing students’ critical thinking and scientific literacy remains a persistent challenge in physics education, particularly in kinematics, where conceptual understanding and problem-solving must be integrated. Although Problem-Based Learning (PBL) has been widely adopted to promote higher-order thinking, limited evidence exists regarding its integration with interactive three-dimensional digital environments. This study investigated the effectiveness of Scratch 3D–supported Problem-Based Learning in enhancing senior high school students’ critical thinking and scientific literacy. A quasi-experimental design was implemented with one experimental group and two control groups involving Grade XI students at a public senior high school in Indonesia. The assessment instruments were rigorously validated and administered before and after the intervention. The findings demonstrate that students who participated in Scratch 3D–supported PBL achieved substantially greater improvements in both critical thinking and scientific literacy than those receiving conventional instruction. The interactive learning environment enabled students to visualize abstract kinematics concepts, engage more actively in problem-solving, and construct deeper conceptual understanding. These findings suggest that integrating interactive Scratch 3D technology into Problem-Based Learning provides an effective instructional approach for fostering higher-order thinking and scientific literacy in secondary physics education